OPTICAL ILLUMINATION WATERMARKING USING DB WAVELET - Singh, Parvinder; Chhikara, Meenakshi (European Scientific Journal, ESJ, 2014)
We proposed a new technology with which real world object can be prevented from illegal photographing. In optical illumination watermarking we have used Db10 wavelet to make the watermark pattern invisible to human eye and also to have 100% accuracy forreading out embedded data. Various different images have been used for generating watermark pattern of various pixel size viz. 2x2, 4x4, 8x8, 16x16. The result revealed that Db10 is effective technique to be used in optical illumination watermarking.